(untitled) (Politeja, 2025)
The election of President Moon Jae-In in 2017 opened an opportunity to improve inter-Korean relations. North Korea’s participation in the 2018 Winter Olympics in Pyeongchang, South Korea, became a turning point in the warming of relations between the two Koreas. The aim of the article is to present selected problems related to inter-Korean dialogue during the administration of President Moon Jae-In, which consisted of many initiatives aimed at undertaking negotiations for dialogue, understanding and cooperation. The theoretical tool used to analyze the above issues is the historical method and the comparative method. The first part of the article presents an outline of the history of inter-Korean dialogue, presenting the positions of the South Korean presidential administrations from President Park Chung Hee to Park Geun Hye. This part is a retrospective evaluation of the previous South Korean policies that sought to engage and cooperate with the North, with special attention to Kim Dae Jung’s ‘Sunshine Policy,’ and Roh Moo Hyun’s ‘Peace and Prosperity Policy,’ with both administrations engaging in inter-Korean dialogue and cooperation to resolve the problem of North Korean nuclear weapons through diplomatic means. The last half of the article describes Moon Jae-In’s Korean Peninsula Peace Initiative (KPPI) and Inter-Korean Summits in 2018. Diplomacy between North and South Korea continued at a brisk pace in 2018, and concluded with the Fifth Inter-Korean Summit in Pyeongyang. President Moon served as a direct mediator between the United States and North Korea. The similarities and differences between conservatives and progressives and their policies toward North Korea, and the elements of the Inter-Korean Summits in 2000, 2007, and 2018, followed by subsequent successes and failures of each administration, reveals vulnerabilities in the policies of reconciliation and openness with the North, the internal debates in South Korea derived from a contestation between ideological elements of ethno-centric nationalism and state-centric nationalism, and the structural factors leading to North Korean belligerence.